Educação e segurança nacional no Brasil e Argentina (1969-1981) - Silva, Thaíse dos Santos (2018)
The research analyzes, in a comparative way, the Brazilian and Argentine dictatorships in the period of Emílio Garrastazu Medici and Jorge Rafael Videla (1969-1981) governments, in order to identify traits of anti-communism in educational policies focused on Basic Education, which resulted in authoritarian practices in Schools and political persecution. In this period, Argentina and Brazil were immersed in the context of the Cold War, which presented itself through disputes over hegemony and influence between the capitalist bloc represented by the US and the communist, led by the USSR. The research also sought to understand how education became one of the most targeted fields by the military in power influenced by the ideology of National Security in combating Marxist infiltration. Governments have instituted changes in curricula, educational legislation, and defined behavioral practices in school communities in both countries. The main thrust was that the enemy would be scattered and disguised in the social milieu and could be a national, with school being an important place for the dissemination of ideas to be fought. Based on the comparison of school policies and practices in these two Latin American countries, which have lived and lived with difficulties resulting from income concentration, inequalities and poverty increase, we sought to examine the similarities and singularities as well as differences in the form of organization And execution of an authoritarian Basic Education. Among the main sources, we selected resolutions, leaflets, decrees, minutes, reports, denunciations, interviews, judicial processes and bulletins of the armed forces of the two countries.